A pictorial guide to the ultrasound identification and assessment of uterosacral ligaments in women with potential endometriosis. Issue 3 (9th August 2019) - Leonardi, Mathew; Condous, George
Abstract: We believe the uterosacral ligaments (USLs) are an essential key to resolving the dilemma of diagnosing endometriosis non‐invasively. This editorial will utilise laparoscopic and ultrasonographic figures and videos, along with written descriptive techniques, to educate clinicians, sonographers, sonologists and radiologists on normal and abnormal USLs to improve knowledge and skill in scanning patients with possible endometriosis.